Three-dimensional analysis of pile behaviour - Chan, Chee Wei. (2010)
Often, any form of ground activities will have an influence on the structures which the ground carries and in some instances of piles, an induced lateral load may act on the piles. Serviceability limit of the pile may be undermined resulting in cracks in the pile or in more disastrous cases, ultimate limit state of the pile will be reached and the pile fails. Numerous research have been carried out to investigate the effects of such lateral loads on piles and in this project, a numerical study has been attempted to understand the effects of lateral soil movement on pile behaviour. Three dimensional numerical analyses were carried out with the use of a finite element analysis program, PLAXIS 3D Foundation. The versatile software was proven to be able to assist in investigating the underlying problem. Three-dimensional models of an embankment were built and a special feature, “embedded pile” was used in the model. The results of the analyses match well with the proposed parametric studies from the literature. The parameters studied were embankment pressure, clay thickness, pile stiffness, soil undrained shear strength and modulus of elasticity of clay. For all the parameters, the bending moment of the pile proved to be very sensitive to any degree of changes while the deflections of the pile were less significant. The study also indicated that the “embedded pile” feature in PLAXIS 3D Foundation was not suitable to model pile group behaviour.